Pendidikan Pancasila Sebagai Pemersatu Perbedaan Melalui Pembelajaran Interaktif di SDN Cijantung 03 Pagi - Sidik, Sendy; Safinatunnajah, Hanifah; Amelia, Rahma; Qoirunisa, Rahma; Deliana, Deliana; Weking , Fransiska Bare; Shafiyah , Salwa Ahda; Hardiyanto , Lutfi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
This community service activity addresses the value of the third principle of Pancasila through Pancasila Education, a unifying principle, utilizing interactive learning. The main issues raised are students' lack of understanding of the meaning of unity and the suboptimal use of learning strategies that directly foster tolerance, cooperation, and respect for diversity. This community service activity provides a solution to these problems: the use of an interactive learning model focused on student-centered activities, such as educational games, group discussions, and project-based learning. The results of this community service activity demonstrate that interactive learning can increase student participation, empathy, and awareness of the importance of unity in social life. Furthermore, this learning approach can foster a collaborative and inclusive learning environment, proven to strengthen positive interactions between students. Overall, this community service activity concludes that the integration of interactive learning into Pancasila Education has proven effective in internalizing Pancasila values, particularly the value of unity, and can enhance social cohesion within the school environment.